2011
DOI: 10.1007/s11240-011-0012-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of saikosaponins in adventitious roots of Bupleurum chinense by semi-continuous culture

Abstract: The influence of semi-continuous culture on root growth and production of saikosaponins was investigated using root cultures of Bupleurum chinense DC. When fresh medium, consisting of half-strength of Murashige and Skoog liquid medium and 5% sucrose, was added at day 30, numerous new young roots developed and grew. Also, an increase in root weight and the total amount of saikosaponins was observed at day 60. Both the concentration and time of adding sucrose to the culture medium had significant effects on root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…However, when examining the different levels of sucrose within each type of closure, we found that sucrose-free medium associated with PTFE membranes had the highest levels of the active principle (20E), which was a significant accumulation (Table 3). These results differ from those described by Hao and Guan (2012), where the addition of sugars increased the accumulation of secondary metabolites. However, these authors worked with adventitious roots whereas we worked with the whole plant.…”
Section: Conditions That Enhance Photoautotrophy Induced Greater Levecontrasting
confidence: 99%
“…However, when examining the different levels of sucrose within each type of closure, we found that sucrose-free medium associated with PTFE membranes had the highest levels of the active principle (20E), which was a significant accumulation (Table 3). These results differ from those described by Hao and Guan (2012), where the addition of sugars increased the accumulation of secondary metabolites. However, these authors worked with adventitious roots whereas we worked with the whole plant.…”
Section: Conditions That Enhance Photoautotrophy Induced Greater Levecontrasting
confidence: 99%
“…Instead of using the initial sucrose concentration, Hao and Guan (2012) showed that controlling sucrose concentration by multiple addition of fresh sucrose at different time points can enhance the adventitious roots proliferation and saikosaponin production of Bupleurum chinense.…”
Section: Sucrose Concentrationmentioning
confidence: 99%
“…Taxol (plaxitaxol): The bark of the taxus tree (Taxus wallichiana) produces a complex diterpene alkaloid which is a potent anticancer agent because of its unique mode of action on Artemisia annua Artemisinin Callus [66] Artemisia Annua Artemisinin Callus [67] Aspidosperma ramiflorum Ramiflorin Callus [68] Azadirachta indica Azadirachtin Suspension [69] Azadirachta indica Azadirachtin Anther culture [70] Azadirachta indica Azadirachtin Suspension [71] Azadirachta indica Azadirachtin Hairy root [72] Azadirachta indica Azadirachtin Hairy root [73] Brucea javanica Cathin Suspension [74] Bupleurum falcatum Saikosaponins Root [75] Bupleurum chinensis Saikosaponins Root [76] Camellia chinensis Flavones Callus [77] Capsicum annum Capsiacin Callus [78] Capsicum chinense Capsiacin Suspension [79] Capsicum chinense Capsiacin Cotyledon [80] Capsicum chinense Capsiacin Suspension [81] Cassia acutifolia Anthraquinones Suspension [82] Aloe barbadensis Anthraquinone Callus [83] Morinda citrifola Anthraquinone Suspension [84] ( Table 1). Continued.…”
Section: Production Of Bioactive Natural Products Using Tissue Culturmentioning
confidence: 99%